Reusable Localized Surface Plasmon Sensors Based on Ultrastable Nanostructures - Vogel, Nicolas; et al. (Small, 2010)
Nanoparticle arrays created by nanosphere lithography are widely used in sensing applications since their localized surface plasmon resonances are extremely sensitive to changes in the local dielectric environment. A major drawback for any biologically oriented sensing application of conventionally produced particle arrays is the lack of stability of the nanoparticles in aqueous media and buffer solutions. Here, a robust and reusable nanoscale sensing platform based on localized surface plasmon resonances of gold nanoparticles embedded in a silicon dioxide matrix is presented. The architecture exhibits extremely high stability in aqueous environments and can be regenerated several times by simple mechanical cleaning of the surface. The platforms surface is ultraflat by design, thus making it an ideal substrate for any bio-oriented sensing application.
Keywords: embedded nanoparticles; hybrid materials; localized surface plasmon resonance; nanosphere lithography; sensors